2021
DOI: 10.1016/j.medj.2021.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in T and B cell function persist in convalescent COVID-19 patients

Abstract: Background Emerging studies indicate that some COVID-19 patients suffer from persistent symptoms including breathlessness and chronic fatigue; however the long-term immune response in these patients presently remains ill-defined. Methods Here we describe the phenotypic and functional characteristics of B and T cells in hospitalised COVID-19 patients during acute disease and at 3-6 months of convalescence. Findings We report that the alteratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
140
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(159 citation statements)
references
References 49 publications
15
140
2
2
Order By: Relevance
“…In line with our findings, a very high proportion of T cells from acute COVID-19 patients express cytotoxic molecules such as Perforin and Granzyme B, with samples of severe patients displaying the highest expression levels (Shuwa et al, 2021). The increased cytotoxic profile persisted for up to six months and was associated with poorer recovery.…”
Section: Proportion Of Activated Cd16 + T Cells and Complement Protein Expression Determines Outcome Of Covid-19supporting
confidence: 90%
“…In line with our findings, a very high proportion of T cells from acute COVID-19 patients express cytotoxic molecules such as Perforin and Granzyme B, with samples of severe patients displaying the highest expression levels (Shuwa et al, 2021). The increased cytotoxic profile persisted for up to six months and was associated with poorer recovery.…”
Section: Proportion Of Activated Cd16 + T Cells and Complement Protein Expression Determines Outcome Of Covid-19supporting
confidence: 90%
“…Descriptions of peripheral blood B cells in the initial weeks of an acute SARS-CoV-2 infection have reported modest relative B cell lymphopenia, and variable increases in plasmablast frequencies, in some cases exceeding 30% of total B cells, reminiscent of findings in other severe acute viral illnesses such as Ebola virus infection ( Kaneko et al., 2020 ; Mathew et al., 2020 ; McElroy et al., 2015 ). These B cell subset changes are consistent but transient, as reported in a longer follow-up study of COVID-19 patients that analyzed plasmablast frequencies within 7 days of hospitalization, at discharge, and after 3 to 6 months of convalescence ( Shuwa et al., 2021 ). This study confirmed the finding of elevated plasmablasts in acute COVID-19 but reported that plasmablasts returned to baseline frequencies in convalescent samples 3 to 6 months after infection.…”
Section: B-lineage Cells In Sars-cov-2 Infectionsupporting
confidence: 80%
“…Another study concludes that changes in B and T cell function following hospitalisation due to COVID-19 could affect immunity in the longer term (up to 6 months) and contribute to some persistent symptoms observed in patients convalescing from COVID-19. (23) Our findings are that 90% (67 out of 74) of patients with LC still have specific cellular immunity more than 7 months after primary infection (78% after more than 9), and there is scope to consider that in the majority of LC patients, cellular immunity could go on for a longer period. The fact that there is prolonged specific T cell activity could be an indirect indicator of viral persistence in LC patients.…”
Section: Specific Cellular Response To Sars-cov-2 In Lc Patientsmentioning
confidence: 70%
“…The fact that there is prolonged specific T cell activity could be an indirect indicator of viral persistence in LC patients. (23) Half of the surveyed LC patients appear to have a 'defective' CD4+ T lymphocyte response, which would prevent CD8+ T lymphocytes from activating adequately, thereby affecting proper antibody production.…”
Section: Specific Cellular Response To Sars-cov-2 In Lc Patientsmentioning
confidence: 99%